2002
DOI: 10.3390/s20900366
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Characteristics of Ag Doped CuO-BaTiO3 CO2 Sensors

Abstract: Abstract:In this paper the characteristics of a CuO-BaTiO 3 based CO 2 gas sensor was investigated. The sensitivity of the CuO-BaTiO 3 based CO 2 sensor was influenced by doping various metal elements such as Au, Ag, Pt, Pd, Ce, Mg, Sr, La, Zn, Fe and Bi, which were added as a pure metal or in the form of metal oxides. It was found that Ag is the most suitable additive among all substances tested. The Ag-doped CO 2 gas sensor has better sensitivity and lower operating temperature, with a detection concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Because C-axis of CuO cell is longer than the length of other two axes, the long axis (C-axis) orients in a direction perpendicular to the film plane. The gas sensitivity (S=ρ gas /ρ air )) is defined as the ratio of resistivity measured at particular gas (ρ gas ) to that of air (ρ air ) [1][2][3]. Graphs between the sensitivity measured at CO 2 gas and time for CuO films sputtered at 192 0 C under 9 (thick solid line), 7.5 (thin solid line) and 6 mbar (dashed line) pressures are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because C-axis of CuO cell is longer than the length of other two axes, the long axis (C-axis) orients in a direction perpendicular to the film plane. The gas sensitivity (S=ρ gas /ρ air )) is defined as the ratio of resistivity measured at particular gas (ρ gas ) to that of air (ρ air ) [1][2][3]. Graphs between the sensitivity measured at CO 2 gas and time for CuO films sputtered at 192 0 C under 9 (thick solid line), 7.5 (thin solid line) and 6 mbar (dashed line) pressures are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thin films of CuO find some potential applications in solar energy converting devices, electro-chromic devices, transparent conducting devices, gas sensors [1][2][3][4] and superconducting devices [5]. Annealing effects on the properties of Copper oxide thin films prepared by chemical deposition have been studied [6].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the higher dispersion of Ag particles which are attained by sintering at higher temperature where the decomposition of AgNO 3, starting material is promoted by increasing the sintering temperature. Jiao et al [19] stated that, low a sintering temperature or too short sintering time is disadvantageous to the decomposition and separation of AgNO 3 . So the increase in the sensitivity with silver additions may be due to the role of silver as a catalytic one on the surface of BaTiO3-CuO through the formation and decomposition of silver carbonates which leads to the significantly increasing sensitivity.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…In this context, the properties of BaTiO 3 -CuO as a sensitive material under carbon dioxide atmospheres have been investigated [1][2][3][4][5][6][7][8][9][10]. Thick film technology and sintering are used to synthesize the material in most of the research works [4][5][6][7][8][9][10], while thin film technology is only reported by the authors [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Thick film technology and sintering are used to synthesize the material in most of the research works [4][5][6][7][8][9][10], while thin film technology is only reported by the authors [1][2][3]. Thin film technology shows advantages in terms of controllability of the process parameters and material properties.…”
Section: Introductionmentioning
confidence: 99%